Isolation and Identification of Cryptosporidium sp. by Reverse Osmosis System of Tap water in Baghdad (Baghdad Science Journal, 2025)
A total of 60 samples of drinking water filtrated by Reverser 0smosis Filtration System from April to October 2012, from different houses in Baghdad – Al Resafa, so as to identify the eggs and cysts of protozoa. Two methods applied direct smear and staining technique with zeal nelson stain, which appeared Tape warm eggs, Ascaris lumbrecoides eggs and oocyst of Cryptospordium sp. This study revealed that total contamination rate with intestinal parasites in tap water were 96.6% this high rate, refers to filtrate tap water by reverse osmosis system was useful to prevent or reduce the contamination of drinking water, in order to reduce risks to public health; So recommended to apply this method at water purification stations. Distribution of Cryptosporidium sp. as study months of year appeared that Spring (April& May ) were recorded the highest rate of contamination in filtrate tap water samples, that due to potential temperatures degrees for this protozoa as(20-30cº).When the drinking water was better as environmental maintained decreased the infection with these parasites.